TRAINING IN MODELLING OF WRITTEN BUSINESS TEXTS - Kulgildinova, Tulebike; Balgazina, Bakhitgul (Acta Neophilologica, 2013)
The article deals with the problem of teaching students (both native speakers and foreigners) how to model and write business texts. The paper also describes the main characteristics of the organization of a text document. In order to make the business text the effective means of achieving a communicative goal, it is necessary to have special strategies and tactics of the discourse: strategy of informing, encouraging strategy, the strategy of persuasion, and strategy commitments. Knowledge of the discursive strategies and tactics of written business communication, as well as the laws that form the content aspect of writing and the ability to use them in accordance with the purposes and conditions of communication is the key to successful business communication in Russian.